Dose Efficiency of Quarter-Millimeter Photon-Counting Computed Tomography: First-in-Human Results. Issue 6 (June 2018) - Pourmorteza, Amir; Symons, Rolf; Henning, André; Ulzheimer, Stefan; Bluemke, David A.
Abstract : Purpose: The aim of this study was to assess the clinical feasibility, image quality, and radiation dose implications of 0.25-mm imaging mode in a cohort of humans, achieved by dividing the photon-counting detector (PCD) size in half compared with standard-resolution photon-counting computed tomography (CT) (0.5 mm). Methods: In this technical feasibility study, a whole-body prototype PCD-CT scanner was studied in the 0.25 mm detector mode (measured at isocenter). A high-resolution PCD-CT protocol was first tested in phantom and canine studies in terms of image noise and spatial resolution. Then, 8 human subjects (mean age, 58 ± 8 years; 2 men) underwent axial PCD 0.25-mm scans of the brain, the thorax, and at the level of the upper left kidney. Filtered backprojection reconstruction was performed with a sharp kernel (B70) for standard-resolution and high-resolution data at 0.5-mm isotropic image voxel. High-resolution data, in addition, were reconstructed with an ultrasharp kernel (U70) at 0.25-mm isotropic voxels. Results: Image reconstructions from the PCD 0.25-mm detector system led to an improvement in resolution from 9 to 18 line pairs/cm in a line pair phantom. Modulation transfer function improved from 9.5 to 15.8 line pairs/cm at 10% modulation transfer function. When fully exploiting this improvement, image noise increased by 75% compared with dose-matched 0.5-mm slice PCD standard-resolution acquisition. However, when comparing with standard-resolution data at same in-plane resolution and slice thickness, the PCD 0.25-mm detector mode showed 19% less image noise in phantom, animal, and human scans. Conclusion: High-resolution photon-counting CT in humans showed improved image quality in terms of spatial resolution and image noise compared with standard-resolution photon-counting. Abstract : Supplemental digital content is available in the text.